High dose steroid and acute visual loss: case report and discussion on acute central serous chorioretinopathy in elderly - Zain, Ayesha M.; Din, Norshamsiah M.; Mushawiahti, M. (International Journal of Basic & Clinical Pharmacology, 2017)
Central serous chorioretinopathy (CSCR) is one of sight-threatening side effects of systemic steroids. Although it is uncommon, CSCR seriously threatens the patient’s vision and it has the potential for permanent visual morbidity. This article reports about a 54-year-old Malay gentleman who developed central vision loss after received a course of oral prednisolone 50 mg/day for a month period for the treatment of multifocal motor neuropathy. His vision recovered 1 year after cessation of steroid as the CSCR resolved. However, subjectively the visual quality is poor. Steroids in any route of administration can induce CSCR and it must be used with precaution especially in the elderly. Although resolutions are usually spontaneous after cessation of steroid, chronic and recurrent CSCR can lead to irreversible visual impairment. Judicious use of systemic steroids, early detection and prompt co-management with the treating physician can help prevent permanent visual disturbance.